Airborne infection risk of nearby passengers in a cabin environment and implications for infection control. Issue 47 (May 2022) - Wang, C.T.; Xu, J.C.; Fu, S.C.; Chao, Christopher Y.H.
Abstract: Background: Expiratory droplets cause high infection risk to nearby passengers via airborne route. Methods : We built a two-row four-seat setup to simulate a public transport cabin. A cough generator and a nebulizer were used to simulate the cough and talk processes respectively. Exposure and infection risk of nearby passengers was studied. The effect of gasper jet and backrest on risk mitigation was investigated. Results: For the activity of coughing, the front passenger has much higher infection risk, which was around four times of that of other passengers, because of the concentration surge in the inhalation zone. For talking, the nearby passengers have similar infection risk because nearby passengers were all exposed to concentration surges with similar peak value. Gasper jet of the infected passenger and higher backrest can extinguish or reduce the concentration surge of front passengers and reduce the infection risk due to coughing and talking droplets. Conclusion: The passengers near the infected passenger have very high infection risk. The overhead gasper and a higher backrest can reduce the exposure and mitigate the risk of infection. It is believed that the control measures to protect nearby passengers are urgently needed in public transport cabins. Highlights: A four-seat setup and airduct system were built to simulate public transport cabin. Airborne concentration near passengers' noses from both cough and talk was counted. Airborne infection risk of each passenger near infected passenger were studied. Effects of overhead gasper and backrest height on mitigating risk were evaluated. Nearby passengers have high risk, and gasper jet or higher backrest was suggested.